Kobieta dla kobiety (w świecie islamu) - Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The aim of this paper is presentation of the feminism activity of elected representatives in the world of Islam for women living in this world. Where we have discrimination against women on account of the sex, sooner or later we have a reaction of the subordinated group dissatisfied with such a state of affairs. Therefore we have the feminist activity in Muslim societies. One should emphasize that feminism among Muslim women is very diverse — different among women who believe in God, different among atheists, different in Muslim countries, different among groups of emigrants in the West. A thesis that the woman has the same rights as the man connects all these currents.
Keywords: women; feminism; islam; discrimination; gender equality; emancipation